Pengaruh Permainan Monopoli Terhadap Pengetahuan Kesehatan Gigi dan Mulut pada Anak Sekolah Dasar di SDN Bangetayu Wetan 02 - Septina Dwi Monika; Indra Tri Astuti; Kurnia Wjiayanti (Jurnal Ilmu Kesehatan dan Gizi, 2025)
Kids who don't know much about teeth and mouth health have problems, so it's important to help them learn more through the right sources and methods. The point of this study was to find out how playing Monopoly affected the kids' understanding of teeth and mouth health at SDN Bangetayu Wetan 02. A quasi-experiment non-equivalent control group strategy was used for this quantitative study. The intervention was given to the intervention group through a game of Monopoly, and to the control group through PowerPoint. The Wilcoxon test (paired) and the Mann-Whitney test (unpaired) were used to look at the data. The study's participants were kids between the ages of 8 and 9, with 19 kids from each group chosen through Purposive Sampling. A knowledge quiz about teeth and mouth health was used as the tool. The results of the comparison of the two groups' traits showed that most of the respondents were girls and most of them were 9 years old. The intervention group had a p-value of 0.001 (<0.05) for paired bivariate analysis using the Wilcoxon test. This means that there was a significant difference between what they knew about teeth and mouth health before and after the intervention. On the other hand, there was no significant change in the control group, where the p-value was 0.665 (>0.05). The training and control groups both got a p-value of 0.000, which is less than 0.05, on the Mann-Whitney test. There are differences between the two groups in how much they know about teeth and mouth health. It has been shown that learning about teeth and mouth health through monopoly games is more effective than learning through PowerPoint.